Detecção do Mycobacterium leprae pela reação em cadeia da polimerase (PCR) em amostras de tecido e SWAB pós - biópsia de pacientes portadores da hanseníase - ALMEIDA, Maria das Graças Carvalho (Universidade Federal do Pará, 2017)
The Mycobacterium leprae DNA of the samples of tissue fragments and swab pos biopsy conserved in lysis buffer solution 2 and swab pos biopsy conserved in lysis buffer solution 1, removed of leprosy lesions of 20 patients with different clinical forms of the illness, was submitted to the amplification for the PCR, aiming at to evaluate the sensitivity of this method. The extration of the DNA was carried through by the technique of modified phenol-chloroform and had been used for the amplification three pairs of primers, LP1/LP2, R1/R2 and S13/S62 that amplify fragments of 129pb, 372pb and 531pb, respectively. Of the patients in study, 55% were paucibacillary and multibacillary 45%. The PCR with primer LP1/LP2 detected 40%, being 15% PB and 25% MB of the samples conserved in lise 1 and, of the conserved ones in lise 2 had been 15%, being 5% PB and 10% MB; primer R1/R2 detected 15%, with 5% in PB and 10% in MB in lise 1, in lise 2 did not have amplification; primer S13/S62 did not amplify the samples in lise 1 and amplified only 10% in lise 2, being one of each group. The bacilloscopy of skin smears presented positives results for 20% patient dos MB and was negative for all PB; the histophatology was positive for 30%, being 20 % for PB and 10% for MB. The PCR with primer LP1/LP2 left to detect DNA of the Mycobacterium leprae in 60% of the samples, the bacilloscopy in 80% and the histophatology in 70%. Due to reduced sensitivity of the PCR in the samples conserved in lise 2, in this study the best ones resulted had been gotten in samples of swab pos biopsy conserved in lysis buffer solution 1, with DNA extracted for the phenol method chloroform modified and amplified for primer LP1/LP2.